Pengembangan Sistem Penyediaan Air Bersih dengan Metode Appropriate Technology di Kelurahan Mekar Sari Kecamatan Rambutan Pemko Tebing Tinggi - Isranuri, Ikhwansyah; Sitohang, Nur Asnah (Jurnal Riset Hesti Medan, 2021)
Planning for a clean water supply system is a community service program carried out by USU in collaboration with the Dinas Pemberdayaan Masyarakat dan Desa(PMD) of the Pemko Tebing Tinggi. The problem encountered is the unavailability of clean water. This condition can interfere with people's daily activities such as the need for households. The clean water supply system that is implemented is the application of appropriate technology in the sense that it is easy to operate and all components are easy to care for by the public. The purpose of this activity is to provide clean water that meets health requirements, namely colorless, tasteless and odorless. This system is also planned to provide clean water for the next few years. The projection of population growth is also a consideration, which is calculated based on the average population growth data. Based on the Indonesian National Standard (SNI), the need for clean water for a population with a population of 300 households with the household category is 120 liters per person per day, so the water requirement is 1.67 liters/second. The source of water is obtained by digging 15 meters deep by installing 15 concrete rings with a diameter of 80 cm and a height of 100 cm. Then a pump is installed to suck water and then it is pumped into a poly tank (capacity 2100 liters) storage tank which is located at a height of 5-6 meters. Before flowing from the tankÂ  to the pipe, the water is filtered using a filter. For this purpose, a piping installation complete with a valve and a float is designed to automatically close the pipe when the tank is full. The result of water from this system is clean water and suitable for consumption by residents.